HUBUNGAN MAQASHID AL-SYARIAH DENGAN FILSAFAT HUKUM ISLAM - Muannif Ridwan; Surya Gusnadi; Aji Kurniawan (Jurnal el-Qanuniy: Jurnal Ilmu-Ilmu Kesyariahan dan Pranata Sosial, 2023)
This study discusses Maqashid al-Shari'ah relationship with the Philosophy of Islamic Law. In ‎the application of Islamic law, it has a purpose for the benefit of every human being and to ‎avoid mankind from evil both in this world and in the hereafter. The ushul fiqh experts have ‎an opinion about five points or elements that humans must guard and maintain in realizing ‎benefit. These five elements include soul, religion, reason, lineage, and property. This ‎research uses the library research method or also known as research that utilizes data and ‎information sourced from the library or also called library research. This study concludes that ‎maqashid al-syari'ah is an indicator in a product of ijtihad. The position of maqashid al-‎Sharia in Islamic law is very important, all problems that are impossible to solve can be done ‎by using maqashid al-syariah, as a means and tool in understanding the Qur'an and Sunnah. ‎The relationship between maqasid al-syariah and Islamic legal philosophy is very close. If ‎viewed based on the essence of maqashid al-syariah has one goal to be achieved by ‎establishing a law for the benefit of the people and maqashid sharia itself is part of the ‎philosophy of Islamic law. In addition, the relationship between Islamic legal philosophy and ‎maqasid al-syariah is to uphold human dignity on this earth. Therefore, in line with this, all ‎philosophies of Islamic law have become a big house which also contains the subject of ‎maqashid al-syariah as a theory that is used to determine and discover the nature, purpose.‎